3x2 - 7x - 20 = (3x + 5)(x - 4)
3x2-7x+4 = (3x-4)(x-1) when factored
(21x3-23x2-76x-32)/(7x+4) = [3x2(7x4) -5x(7x+4)-8(7x+4)]/(7x+4)=3x2-5x-8
3x2 - 7x + 2 = 3x2 - 6x - x + 2 = 3x(x - 2) - 1(x - 2) = (3x - 1)(x - 2) So x = 1/3 or x = 2
3x2+7-6 = (3x-2)(x+3) when factored
3x2 - 7x - 20 = (3x + 5)(x - 4)
2x² − 7x + 5
(3x + 5)(x - 4)
3x2-7x-20 = (3x+5)(x-4) when factored
(x + 4)(3x - 5)
(3x - 5)(x + 4)
3x2-7x+4 = (3x-4)(x-1) when factored
(21x3-23x2-76x-32)/(7x+4) = [3x2(7x4) -5x(7x+4)-8(7x+4)]/(7x+4)=3x2-5x-8
If that's +7x - 6, the answer is (x + 3)(3x - 2)
It is -2*(3x2 - 7)*(x3 - 7x)-3
3x2 - 7x + 2 = 3x2 - 6x - x + 2 = 3x(x - 2) - 1(x - 2) = (3x - 1)(x - 2) So x = 1/3 or x = 2
If you mean 3x2-7x+x = -4 then there are no solutions because the discriminant of the quadratic equation is less than zero.